Pengembangan Media Pembelajaran Berbasis Game Educaplay Pada Sub Materi Sistem Pencernaan Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VIII SMP - Hadiah Hadiah; Syubhan Annur; Sauqina Sauqina (CV.ITTC INDONESIA, 2026)
The goal of this project is to create an Educaplay-based game that will enhance students' understanding of the human digestive system. The 4D model, which comprised the steps of define, design, and develop, was used in the research and development (R&D) design. Experts verified the media, student answers were used to assess their usefulness, and pre-test and post-test gain scores were used to assess their efficacy. With an average score of 0.86, which is classified as very valid, the validation results showed a high degree of feasibility. 25 eighth-grade children took the practicality test, and they scored 91%, which is considered extremely practical. Students' learning outcomes significantly improved, as seen by the effectiveness test's N-Gain values in the medium to high category. These findings show that using Game Educaplay-based media for junior high school scientific instruction is doable, useful, and successful.